Sharia Financing Education for BKM and UPK in Pekapuran Laut Village, Central Banjarmasin - S. Purnamasari; Purnama Rozak; Nurul Listiyani; Abdul Hadi (Jurnal Pengabdian Pancasila (JPP), 2023)
As with other theories and practices, the theory and practice of Islamic Economics will exist and become a model when it is able to solve problems that occur in society, and is abandoned if it is deemed unable to solve problems that occur in society, especially the problem of poverty and poverty. unemployment that occurs because of injustice. Starting from this opinion, academics and practitioners of Islamic Economics must always evaluate and improve concepts and practices that are unable to solve problems in society. For this reason, things that need to be done are some improvements related to financing problems, for example improving the quality of the financing system, opening up financing concepts that are still possible to be rolled out, procedures that are easier and remain prudent. For example, burdensome procedures such as the existence of a period of employment for a beneficiary of funds/creditors who submit an application need to be changed by providing assistance. So it's not refusing productive financing applications, but accepting it with assistance or with a personal guarantee or ad inman. With this model, employment opportunities will be more open and in turn the welfare of the people will become more widely distributed.